Managers’ risk preferences and firm training investments - Caliendo, Marco [Verfasser]; Cobb-Clark, Deborah A. [Verfasser]; Pfeifer, Harald [Verfasser]; Uhlendorff, Arne [Verfasser]; Wehner, Caroline [Verfasser] (My University, 2024)
„This study analyses the impact of managers’ risk preferences on their training allocation decisions. We begin by providing nationally representative evidence that managers’ risk-aversion is negatively correlated with the likelihood that their firms engage in any worker training. Using a novel vignette study, we then demonstrate that risk-tolerant and risk-averse decision makers have significantly different training preferences. Risk aversion results in increased sensitivity to turnover risk. Managers who are risk-averse offer less general training and are more reluctant to train workers with a history of job mobility. Adopting a weighting approach to flexibly control for observed differences in the characteristics of risk-averse and risk-tolerant managers, we show that our findings cannot be explained by heterogeneity in either managers’ observed characteristics or the type of firms where they work. All managers, irrespective of their risk preferences, are sensitive to the investment risk associated with training, avoiding training that is more costly or that targets those with less occupational expertise or nearing retirement. This provides suggestive evidence that the risks of training are primarily due to the risk that trained workers will leave the firm (turnover risk) rather than the risk that the benefits of training do not outweigh the costs (investment risk).“ (authors‘ abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; 370; 330; Betrieb; Unternehmen; Führungskraft; Bildungsinvestition; Risiko; Betriebliche Weiterbildung; Weiterbildungsverhalten